Abruptly Shifting to More Authenticity: How Three Civics Teachers Leveraged Technology to Engage Their Students at the Beginning of the COVID-19 Pandemic. Issue 2 (12th April 2022) - Duhaylongsod, Leslie; Zetlin, Ariana; Shen, Lisa Utzinger; Allen, Danielle
Abstract: This study investigated how 8th-grade civics teachers kept their students engaged in learning during the abrupt shift to remote teaching caused by the COVID-19 pandemic in the spring of 2020. We analyzed the interview transcripts of 10 teachers who were piloting a new civics curriculum during the 2019–2020 school year. We found that three of 10 teachers leveraged technological tools to offer more authentic learning experiences for their students, which led to increased student engagement online. Implications for practice are discussed.